Entrepreneurs as strategic transformation managers: exploring micro-foundations of digital transformation in small and medium internationalisers - Jafari-Sadeghi, Vahid; Amoozad Mahdiraji, Hannan; Alam, Gazi Mahabubul; Mazzoleni, Alberto (Elsevier, 2023)
This paper is set to explore the role of individual-level behaviours and actions in the digital transformation of international SMEs. This is particularly important since little is known regarding the extent to which entrepreneurs and decision-makers manage the digitalisation process. Thus, building on the theory of planned behaviour, this research focuses on individual-level micro-foundations in the digital transformation of small and medium internationalisers. The paper benefits from a mixed-method synthesis. First, through a systematic review of literature, we identified twenty-seven factors in four inclusive categories. Then, they have been narrowed down to the top seven individual-level micro-foundations, using Intuitionistic Fuzzy Delphi based on Normalised Hamming Distance. Subsequently, Intuitionistic Fuzzy Decision-Making Trial and Evaluation Laboratory analysis is applied to disentangle the causality and effectuality as well as conceptual framework to depict their interrelationships. Our findings contribute to the digital transformation research by developing six prepositions that explore the relationships between SMEs micro-foundations at the individual level.